Problems of long-term therapy of dementia - N. M. Zalutskaya (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2018)
The article discusses the problem of long-term therapy of dementia, provides information on factors playing a role in the formation of commitment to therapy in patients with Alzheimer’s disease, discusses factors that influence the organization of care to patients with dementia. The article presents data on the clinical and economical effectiveness of akatinol memantine and opportunities to improve adherence to treatment at application of a once-daily memantine